ADVANCING SUSTAINABILITY: THE ROLE OF GREEN ECONOMY IN ENVIRONMENTAL CONSERVATION AND RESOURCE MANAGEMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The global community faces unprecedented challenges in balancing economic development with environmental preservation and resource management. The concept of a green economy emerges as a promising solution, integrating sustainable practices into economic systems to foster environmentally friendly growth. This article examines the principles, benefits, and challenges of the green economy paradigm, exploring its potential to mitigate climate change, conserve natural resources, and promote socio-economic well-being. Through a comprehensive review of existing literature and case studies, this paper highlights the transformative power of green economy initiatives and outlines key strategies for its successful implementation in environment and resource management.